2001
DOI: 10.1557/proc-706-z4.7.1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Nanofibre-Filled Thermoplastic Composites

Abstract: Macroscopic poly(ether ether ketone) (PEEK) and polypropylene (PP) nanocomposites containing vapour-grown carbon nanofibres (CNF) were produced using standard polymer processing. Tensile tests revealed a linear increase in composite stiffness with nanofibre content. A detailed DSC study verified that under standard processing conditions the degree of crystallinity and the crystalline structure of these semicrystalline thermoplastics were not affected by the nanofibres. Nevertheless, we provide evidence that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The procedures seem to deserve further improvement; MBG say soberly: with dexterity, bubble formation can be avoided. Nanohybrids-such as those containing carbon nanofibers [6][7][8] -seem much more promising in this respect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures seem to deserve further improvement; MBG say soberly: with dexterity, bubble formation can be avoided. Nanohybrids-such as those containing carbon nanofibers [6][7][8] -seem much more promising in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, words "friction" and "wear" do not appear in the subject index of the Goldman, Mark, or LSM books, while the excellent papers on mechanics hardly venture into tribology. The small number worldwide of groups active in polymer tribology with good results [6][7][8] (see also a review of the field 16 ) does not change the overall situation in a decisive way.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies [9,10] we have shown that vapour-grown carbon nanofibres (CNF) can be homogeneously incorporated and dispersed in PEEK composites by twin-screw extrusion and injection moulding. The resulting nanocomposites showed a linear increase in stiffness and strength with increasing nanofibre content.…”
Section: Introductionmentioning
confidence: 99%
“…Their high aspect ratio and graphitization degree make them an attractive choice for the manufacturing of advanced polymeric materials with improved strength and stiffness, as well as some supplementary attributes such as electrical conductivity and improved thermal stability 4, 5, 9, 11. Moreover, vapor grown carbon nanofibers suppose a relatively low cost model system for carbon nanotubes in order to understand their role for load transfer in composites 12…”
Section: Introductionmentioning
confidence: 99%
“…Vapor grown carbon fibers (VGCFs) have been successfully compounded with different thermoplastic9, 10, 12–25 and thermoset26, 27 matrices using conventional polymer processing technology such as high‐shear mixing or extrusion, demonstrating the feasibility of such methods for effective dispersion and orientation of the nanofibers. Unfortunately, the mechanical performance of these composites have been limited by the lack of an adequate interface strength, which results in poor interlaminar adherence and fiber pull‐out 4, 28…”
Section: Introductionmentioning
confidence: 99%